Fabrication of green synthesized lanthanum-doped bismuth ferrite perovskite type nanoparticles for photocatalytic removal of ibuprofen from aqueous solution - Rasmirekha Pattanaik; Rishabh Kamal; Debapriya Pradhan; Suresh Kumar Dash (Discover Applied Sciences)
Abstract Ibuprofen is a potential environmental toxin and carcinogen for freshwater ecosystems, posing significant risks to human health, particularly through its impact on kidney function. This research introduced a new type of bismuth ferrite perovskite material, modified with separable lanthanum, to explore how sunlight can be used to break down ibuprofen in water. The catalysts used in the study were created through green synthesis and co-precipitation methods, and their characteristics were analyzed using various techniques like X-ray diffractometry (XRD), Field Scanning emission microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), UV–VIS absorption spectroscopy (UV-DRS) and Photoluminescence spectra (PL). The green-synthesized 1% La-BiFeO3 nanoparticles achieved ≈89% degradation of ibuprofen under sunlight within 90 min, with a pseudo-first-order reaction. The addition of 1% lanthanum to BiFeO3 increased the material’s surface area and pore capacity significantly, resulting increase in photocatalytic ibuprofen mineralization efficiency. The paper also provides a probable mechanism for how lanthanum doping effects the formation of BiFeO3 nanoparticles and their photocatalytic activity based on experimental data. The catalytic properties of the bio-synthesized La-BFO nanoparticles were then assessed by their ability to degrade under various laboratory conditions. This demonstrates that the phytochemical from moringa oleifera provides an inexpensive and environmentally friendly approach for synthesizing catalytic nanoparticles that can break down highly toxic drugs. Graphical abstract